Tuberculosis of the wrist masquerading as complex regional pain syndrome type 1: A diagnostic dilemma - Ganesh Singh Dharmshaktu; Anshuman Vijay Roy (International Journal of Medical Research and Review, 2014)
Tuberculosis of the wrist region is unusual site and requires high index of suspicion to get a validated diagnosis. The pattern of clinical features and their vagueness contribute to its neglect or misdiagnosis . Various other chronic pain disorders of the wrist can mimic the tubercular affectation of the wrist and vice versa. Complex regional pain syndrome type 1 is the clinical entity that can closely resemble prodromal features of tubercular disease especially in the settings of history of minor trauma and history of consequent immobilization as its treatment.